Analysis of microRNA expression reveals convergent evolution of the molecular control of diapause in annual killifishes - Barth, Emanuel; Baumgart, Mario; Dolfi, Luca; Cui, Rongfeng; Groth, Marco; Ripa, Roberto; Savino, Aurora; Valenzano, Dario Riccardo; Platzer, Matthias; Marz, Manja; Cellerino, Alessandro (Frontiers in Genetics, 2025)
BackgroundDiapause is a condition of developmental arrest in anticipation of adverse environmental conditions present in many diverse taxa. Diapause is a key adaptation that enabled the colonization of ephemeral habitats subject to the alternation of dry and wet seasons by annual killifishes. Upon desiccation of the ponds, killifish embryos remain vital but quiescent in the clay, where they can survive months or even years. Diapause can occur at three different developmental stages, but Diapause II (DII), which occurs during somitogenesis, is the primary point of developmental arrest. Physiologically, Diapause II is associated with the arrest of the cell cycle in G1 and deeply reduced oxygen consumption and protein synthesis. However, diapause is not obligatory, and some embryos can go through an alternative developmental pathway into direct development, skipping one or more diapauses. The precise molecular mechanisms that regulate entry and exit from diapause are beginning to be investigated, but this knowledge is yet fragmentary. Diapause has evolved independently several times in killifish clades from Africa and South America, enabling identifying possible molecular determinants of diapause by comparative expression analysis. MicroRNAs are small RNAs that represent central nodes in the control of gene expression at the post-transcriptional level and are involved in many developmental processes. Here, we compare microRNA expression profiles of annual killifishes during DII with non-annual killifish in a comparable stage of morphological development.ResultsWe used smallRNA-Seq to quantify microRNA expression from four annual- and four non-annual killifish species from three independent clades and from direct-developing embryos of the annual killifish Nothobranchius furzeri. We analyzed the expression of broadly conserved microRNAs and microRNAs that appear to have evolved in the killifish lineage. We found several microRNAs that showed convergent regulation in the three different clades, and for some microRNAs also a phenomenon of switch in the prevalent form between 3p and 5p or vice versa was noted. In addition, we detected a significant overlap between the microRNA regulation during diapause and aging. Particularly interesting is the regulation of the miR-430 family. These microRNAs represent the second most expressed microRNA family in the killifish embryos, and diapause is associated with dramatic downregulation of the prevalent 3p form and upregulation of the minor 5p form. Members of the miR-430 family are contained in a large repetitive cluster whose organization is variable among teleosts. Analysis of recently sequenced 45 low-coverage killifish genomes revealed that the miR-430 locus contains a lower number of copies in annual-as opposed to non-annual killifish.ConclusionThe Evolution of diapause is reflected in the convergent evolution of microRNA regulation in killifishes. A prominent feature is a dramatic downregulation of miR-430 expression that could be partially explained with a reduction of its copy numbers in the genome.